1985
DOI: 10.1073/pnas.82.16.5295
|View full text |Cite
|
Sign up to set email alerts
|

In vitro mutagenesis of the v-sis transforming gene defines functional domains of its growth factor-related product.

Abstract: The polypeptide sequence of the v-sis transforming gene product of simian sarcoma virus (SSV) can be divided into four regions that are likely to represent structural domains of the protein. Mutations were generated in the SSV nucleotide sequence to assay the extent or function of each of these regions. The results indicate that the helper virus-derived amino-terminal sequence as well as a core region homologous to polypeptide chain 2 ofplatelet-derived growth factor (PDGF) are required for the transforming fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…The connection between dimerization and transformation has recently been described on the basis of two mutants with mutations in the v-sis gene which encode truncated gene products that differ in size by 50 amino acids (17). Our data support previous work with both PDGF and the v-sis gene product, which showed that mitogenic activity was lost upon reduction (20).…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The connection between dimerization and transformation has recently been described on the basis of two mutants with mutations in the v-sis gene which encode truncated gene products that differ in size by 50 amino acids (17). Our data support previous work with both PDGF and the v-sis gene product, which showed that mitogenic activity was lost upon reduction (20).…”
Section: Methodssupporting
confidence: 82%
“…The importance of these Cterminal residues for transformation is not known. A previous report indicated that a truncated 239-amino acid v-sis gene product retains biological activity (17). However, this was only a single endpoint and still retained 19 amino acids beyond the PDGF-homologous region.…”
mentioning
confidence: 99%
“…PDGF BB has been identified as the human homolog of the v-sis oncogene product (4,5,19). The minimal v-sis transforming domain spans 89 amino acids (8,11), contains eight cysteine residues, four of which are involved in intrachain disulfide linkages essential for PDGF function (7,18), and is identical in sequence to PDGF BB. Regions of the molecule specifically involved in PDGF receptor binding and activation have yet to be elucidated.…”
mentioning
confidence: 99%
“…Sequences encoding the remaining 219 amino acids are derived from the woolly monkey PDGF B gene (6). Site-directed mutagenesis has identified the minimum transforming region of v-sis as an 89-codon stretch (12,17). More recent studies have further localized this region to 84 codons bound by cysteine codons (unpublished).…”
Section: Resultsmentioning
confidence: 99%
“…PDGF BB has been identified as the human homolog of the v-sis oncogene product (7,26,33). The minimal v-sis transforming domain spans 89 amino acids identical in sequence to human PDGF B (12,17) and contains eight cysteine residues, four of which are involved in intrachain disulfide linkages essential for PDGF function (8,31).…”
mentioning
confidence: 99%